Analisis kemampuan berpikir kreatif siswa dalam menyelesaikan soal open ended berdasarkan kemampuan pemahaman matematis - Samuntya, Fitri; Susiswo, Susiswo; Muksar, Makbul (Jurnal Kajian Pembelajaran Matematika, 2022)
This study aims to describe students creative thinking abilities in solving open ended problems based on mathematical understanding abilities. This type of reasearch is a qualitative descriptive study. The subjects of this research were 6 seventh grade students of SMP Muhammadiyah 4 Malang selected based on their mathematical understanding abilities. Test and interview were employed to collect data. The results showed that aspect of fluency could be achieved by students with high, medium, and low mathematical understanding abilities. The aspect of flexibility could be achieved by students who have high and medium mathematical understanding abilities. Finally, the aspect of originality could only be achieved by students with high mathematical understanding abilities.